Book Review: Leonard Harris, A Philosophy of Struggle: The Leonard Harris Reader. Edited by Lee A. McBride III (London: Bloomsbury Academic, 2020). - Duncan R. Cordry (Journal of French and Francophone Philosophy, 2021)
The following paper serves as a review of a recent compilation of essays by Leonard Harris (edited by Lee A. McBride III), addressing the reimagining of philosophy contained therein and engaging a handful of views borne by this unique philosophical conception from a Deleuzo-Guattarian perspective, focusing on a few of the strategic merits and challenges faced by a potential alliance between these thinkers.